The Reasons of Emigration of Russians from Lithuania: Research Overview, Analysis of Press and Interview Data - Marcinkevičius, Andrius; Frėjutė-Rakauskienė, Monika (Information & Media, 2021)
The causes of the emigration of the members of the Russian ethnic minority from Lithuania in the last two decades are analyzed in the article. There is a lack of official statistics about the scale (numbers) and reasons for the emigration of ethnic minority groups from Lithuania. Therefore, the qualitative data analysis of Lithuanian press in the Russian language and interviews with informants of Russian nationality is presented in the article. The qualitative data analysis allows to look at the aspects on emigration from the Russian ethnic minority group perspective. The topics of articles about emigration and emigration aspects reflected in informants’ interviews are analyzed. It is considered how emigration of Russians from Lithuania is related to socio-economic, socio-psychological and other factors important to the country’s development.
Keywords: Russian ethnic group; emigration from Lithuania; reasons for emigration